Smartening Up with Artificial Intelligence in Dentistry: A Review - Paulose, Anoopa; R, Jayalakshmi M; Thampy, Anu Merlin; Kurian, Christy Mariam; Alias, Ankitha Miria; Aluckal, Eby (Journal of Orofacial Research, 2022)
Artificial intelligence is gaining popularity around the world as a high-impact, game-changing breakthrough in the field of intelligence innovation. It is used in a variety of fields, ranging from automation to dentistry. It is a lifeline for dentistry, especially in the field of prosthodontics, as it aids in the creation of functional maxillofacial appliances and the design of prostheses. It also aids in the recording, diagnosis, treatment planning, and patient management processes, allowing oral health care professionals to work smarter rather than harder. This paper discusses the prosthodontic issues and obstacles that come with total denture construction. It also emphasises advancements in digital technology in prosthodontics, artificial intelligence in dentistry in general, and methods that have been implemented to improve the oral health-care system.